2018
DOI: 10.1016/j.trecan.2017.11.007
|View full text |Cite
|
Sign up to set email alerts
|

DISE: A Seed-Dependent RNAi Off-Target Effect That Kills Cancer Cells

Abstract: Off-target effects (OTEs) represent a significant caveat for RNAi caused by substantial complementarity between siRNAs and unintended mRNAs. We now discuss the existence of three types of seed-dependent OTEs (sOTEs). Type I involves unintended targeting through the guide strand seed of an siRNA. Type II is caused by the activity of the seed on the designated siRNA passenger strand when loaded into the RNA-induced silencing complex (RISC). Both type I and II sOTEs will elicit unpredictable cellular responses. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 66 publications
2
28
0
Order By: Relevance
“…Consistently, miR-34a exhibits low toxicity to normal cells in vitro and in vivo (Di Martino et al, 2012). If one assumes most of its toxicity comes from its toxic 6mer seed sequence, these reports are consistent with our observation that mice treated with toxic siRNAs while slowing down tumor growth showed no signs of toxicity to normal tissues (Murmann et al, 2017). In contrast, in cancer cells miR-34a,b,c become highly expressed after genotoxic stress as they are p53-regulated (He et al, 2007).…”
Section: Mir-34a and Its Clinical Utilitysupporting
confidence: 90%
See 2 more Smart Citations
“…Consistently, miR-34a exhibits low toxicity to normal cells in vitro and in vivo (Di Martino et al, 2012). If one assumes most of its toxicity comes from its toxic 6mer seed sequence, these reports are consistent with our observation that mice treated with toxic siRNAs while slowing down tumor growth showed no signs of toxicity to normal tissues (Murmann et al, 2017). In contrast, in cancer cells miR-34a,b,c become highly expressed after genotoxic stress as they are p53-regulated (He et al, 2007).…”
Section: Mir-34a and Its Clinical Utilitysupporting
confidence: 90%
“…We had previously postulated that 6mer seed toxicity could be an anticancer mechanism and predicted that small RNAi active guide RNAs would be involved in killing cancer cells (Putzbach, Gao, Patel, Haluck-Kangas, et al, 2017). Consistent with this hypothesis, an analysis of published data on point mutations in the exomes of 27 different human cancer showed that losing a C is the predominant point mutation across all cancers (Lawrence et al, 2013).…”
Section: Sirnas With Toxic Seeds Target Housekeeping Genes Enriched Imentioning
confidence: 84%
See 1 more Smart Citation
“…Peter and colleagues have identified suicide/killer RNA molecules (siRNA, shRNA, miRNA, siRNA+miRNA complex) on numerous cancer types. In addition, they have shown that specific toxic RNAi-active sequences present in the genome can kill cancer cells [40][41][42][43][44]. Rozowsky and colleagues have generated a comprehensive analytic platform for extracellular RNA profiling called "exceRpt" [45].…”
Section: Application Field Of Omics Technology In Molecular Medicinementioning
confidence: 99%
“…We called this form of cell death DISE, for death induced by survival gene elimination (Putzbach et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%